(untitled) (Research, Society and Development, 2024)
Introduction: This study emphasizes that this scenario of non-cooperation between users and health institutions compromises the effectiveness of treatments, causing harm to society in both the short and long term. Objective: To highlight how harmful the lack of health knowledge on the part of the user becomes, and the use of empirical methods, myths, and beliefs in the treatment of diseases that are used by individuals, without any scientific proof. Methodology: Based on the guiding question: "How does the lack of technical-scientific knowledge on the part of users in health processes, together with stigmas, cultural practices and beliefs without scientific backing, result in adverse impacts?". The narrative review method was used to gather existing studies on the subject and obtain knowledge through a bibliographic review. Final discussion: The techniques passed down from "generation to generation" are generally used by elderly people and individuals with a low level of education, and are based on beliefs and guesswork, most of which go against science, but there needs to be a balance in relation to scientific treatments, so that there is no overuse of medicines. Conclusion: It is extremely important that health professionals instigate this search for knowledge in users in a way that does not diminish their beliefs, for example through casual conversations during routine procedures, so that they seek professional advice before starting any type of health treatment.